Empty Sella, Full Story: Delayed Recognition of Sheehan’s Syndrome in a Middle-Aged Woman: Delayed recognition of Sheehan syndrome in a middle-aged woman (Indian Journal of Case Reports, 2026)
Sheehan’s syndrome is a rare but important cause of hypopituitarism that may present years after postpartum hemorrhage with vague, nonspecific symptoms, often leading to delayed diagnosis. A 53-year-old woman from Assam presented with persistent nausea, recurrent non-bilious vomiting, and severe hyponatremia. Initial evaluation revealed esophageal candidiasis, hypotension, dehydration, and elevated inflammatory markers. Scrub typhus IgM was positive, and she improved partially with intravenous doxycycline and fluids. However, hypotension persisted, and hyponatremia recurred after stopping IV fluids, prompting evaluation for adrenal insufficiency. Investigations showed low fasting cortisol with inappropriately low ACTH, suggestive of secondary adrenal insufficiency. Further history revealed postpartum hemorrhage due to retained placenta 20 years earlier, requiring blood transfusion, followed by failure of lactation. Differential diagnoses included tuberculous adrenalitis, given the endemicity of tuberculosis in Northeast India, and late-onset Sheehan’s syndrome. Tuberculosis workup, including Mantoux, sputum AFB, TruNAAT, and adrenal imaging, was negative. MRI brain demonstrated an empty sella, confirming chronic pituitary atrophy consistent with Sheehan’s syndrome. The patient’s presentation was likely precipitated by acute stress from scrub typhus infection, unmasking underlying hormonal insufficiency. Unlike primary adrenal insufficiency, secondary adrenal insufficiency in Sheehan’s syndrome presents with low cortisol and low ACTH but preserved mineralocorticoid function, explaining the absence of hyperkalemia. She was started on hydrocortisone replacement therapy (30 mg/day initially), resulting in normalization of serum sodium, resolution of symptoms, and stabilization of blood pressure. The dose was later tapered to 15 mg/day with regular electrolyte follow-up. This case highlights that Sheehan’s syndrome can present decades after the inciting obstetric event with isolated manifestations such as recurrent hyponatremia, vomiting, and hypotension. A detailed obstetric history, especially postpartum hemorrhage and lactation failure, remains crucial for diagnosis. Early recognition and glucocorticoid replacement are lifesaving and help prevent adrenal crisis. Clinicians should maintain a high index of suspicion for Sheehan’s syndrome in middle-aged women with unexplained endocrine or metabolic abnormalities, particularly in regions where home deliveries and postpartum hemorrhage remain common